Warping a portrait photo using image morph - Gan, Christopher Kok Hang (Nanyang Technological University, 2023)
This project aims to demonstrate the capabilities of warping a portrait photo using image morphing technique to create a unique and visually stunning effects. The project will utilize Image Morphing algorithm to transform a portrait image into a new warped image, providing a smooth transition visualization effect. The morphing algorithm will be achieved by selecting control points from the original and destination image and transforming them through the interpolation of intermediate images to form the visualization effect. The process and the warped image can be viewed in a Graphical User Interface on MATLAB, allowing users to view the transition and the warped image in real time or adjust the control points if necessary. The application of the image morphing technique can be used in various industries such as entertainment and advertising to create a special effects and realistic animations. Overall, the project aims to exhibit the use of image morphing technique and deliver an easy-to-use tool for anyone who is interested in creating unique and visually stunning warped portraits.